Domestic Violence in Province 3: An Empirical Reference to Case of Women in Pharping, Kathmandu - Poudel, Muna (Journal of Business and Social Sciences, 2018)
The aim of the research is to explore the domestic violence in woman of Pharping, Kathmandu. The descriptive and exploratory research designs have been adopted in the study. The sample has been taken from Sheshnarayan Mahila Bidhyalaya, Pharping, Kathmandu. The study has been focused only on women. The purposive sampling method has been used to collect the information. The descriptive analysis concluded that women in city are still victims of discrimination and domestic violence. There is a great need for the commitment of all people including social workers, organizations, and political institutions to bring an end to all forms of violence against woman.